Penerapan Good Governance dalam Pelayanan Cetak Ulang KTP-el di Kantor Kelurahan Barata Jaya - Ria, Catur Ajeng Kartika; Indartuti, Endang (Universitas Gajah Putih, 2024)
The principle of Good Governance is good governance implemented by the government to provide public services. The implementation of Good Governance through public services is a manifestation that is very close to the community, especially in terms of population administration. Based on this, the aim of this research is to find and analyze the benefits of implementing good governance and the quality of public services in e-KTP reprinting services in Baratajay Village using the main principles of good governance. This research is qualitative research with three data collection methods: interviews, observation, and documentation. The data analysis used in this research draws conclusions from the data collected. The results obtained were the finding that the e-KTP reprinting service at the Baratajaya Village Office was an example of good governance in the form of good population administration services provided by the Baratajaya Village Office to the community. Based on the entire research process, it can be concluded that the e-KTP reprint service applies the main principles of good governance: Participation, Accountability and Transparency. This can be carried out properly and synergy between the Subdistrict Office parties must be maintained.